Active‐matrix mesh electronics thin‐film‐transistor arrays for biometrics‐under‐display and biomedical applications. Issue 5 (5th May 2021) - Kronemeijer, Auke Jisk; Peeters, Bart; de Haas, Gerard; Verbeek, Roy; Bel, Thijs; van de Laar, Robert; Ugalde Lopez, Leslye Astrid; Peters, Laurens C. J. M.; Gelinck, Gerwin H.
Abstract: A monolithic manufacturing process is presented for the realization of active‐matrix meshed thin‐film‐transistor (TFT) arrays on foil with physical voids between pixels, realizing membrane‐like electronic arrays. The process is scalable to large‐area substrates and enables (improved performance of) biometrics‐under‐display applications. Moreover, membrane‐like TFT arrays provide opportunities for the use of TFT technology, and broader large‐area thin‐film electronics, in new applications in the domain of biomedical electronics, as demonstrated by example use cases of in vivo electrophysiology of the brain as well as in vitro electrophysiology in smart microwell plates. Abstract : A monolithic manufacturing process is presented for the realization of active‐matrix meshed TFT arrays on foil with physical voids between pixels. Membrane‐like TFT arrays enable improved performance of biometric‐under‐display applications and, moreover, provide opportunities for the use of TFT technology in the biomedical domain, such as e.g. brain‐computer interfacing and Organ‐on‐Chip.